Cotton fabric functionalized with nanostructured MoS2: Efficient adsorbent for removal of Pb, Hg, Cd and Cr from water. Issue 6 (December 2022) - Abouda, I.; Walha, S.; Bouattour, S.; do Rego, A.M. Botelho; Ferraria, A.M.; Sousa, A.S.C.; Costa, N.; Boufi, S.
Abstract: In the present work, nanostructured Molybdenum disulphide (MoS2 ), supported on a cotton fabric, was prepared in situ via a hydrothermal approach using ammonium heptamolybdate and thiourea as precursors, combining the mechanical strength and flexibility of cotton textile with the outstanding adsorption performance of layered MoS2 . Evidence for the in situ generation of crystalline MoS2 at the cotton fibres surface was obtained by XRD, Raman and XPS spectroscopies and the morphology of the appended MoS2 layer was analysed by FESEM microscopy, revealing a flower-like structure uniformly grown onto the cotton fibres. Batch adsorption experiments have demonstrated the effective adsorption of Hg(II), Pb(II), Cd(II) and Cr(VI) from aqueous solutions within a short time (less than 15 min) and with adsorption capacities between 300 and 1200 mg/g, depending on the metal ion. A distribution coefficient (Kd ) exceeding 10 4 was achieved for Hg, Pb and Cd, confirming the exceptional adsorption efficiency of the hybrid structure, made of cotton and MoS2 (Cot-MoS2 ), for these classes of highly toxic heavy metal ions. A Langmuir model was fitted to kinetics experimental results through a non-linear least square fitting with good correlation values. Isotherm studies showed that the adsorption process, while well described by a Langmuir model, was better described by a Sips equation mixing Langmuir and Freundlich adsorption models, the exponent α, being not very different from 1, confirms that the dispersion of energy adsorption is not very large. As a proof-of-concept for the potential applicability of the hybrid structure Cot-MoS2 for the in-flow water decontamination from toxic heavy metal ions, a column filled with Cot-MoS2 was tested under continuous filtration conditions, achieving a removal efficiency of more than 99%. Graphical Abstract: ga1 Highlights: Hybrid cotton fabric-MoS2 was prepared by hydrothermal treatment at 150 °C. The appended MoS2 on the cotton fibres exhibited a flower-like morphology. The Cotton-MoS2 demonstrated exceptional adsorption capacity and affinity toward Hg, Pb and Cd ions. Kinetics data are well described by Langmuir non-linear fittings. Adsorption isotherms are well described by a Langmuir-Freundlich model with α ≈ 1.